The Good Clinical and Research Practices course endorsed by the National Council for Health Research of Costa Rica: reflections concerning the field of psychology - Fernández Fernández, Daniel (2022)
Introduction: This article seeks to systematize and make effective the concerns and debates generated from the implementation of the Good Clinical and Research Practices course that psychologists must currently take in order to be accredited by the National Council for Health Research (CONIS) in compliance with the requirement of the Biomedical Research Regulation Law (No. 9234).  Objective: To this end, the research seeks to identify the value that members of the academic and student community of the School of Psychology of the University of Costa Rica have on the approach to bioethics, health and the therapy in the framework of this course. Likewise, the objective is to learn the criteria that the academic community considers essential for the development of a course of this nature.  Method and technique: The research methodology is qualitative and the data were collected using the problem-centered interview technique. Regarding the information analysis, the assessments made by the people consulted on the content of the Course were typified and then an analysis of the arguments supporting these assessments was developed.  [Continue reading in the article]